DFT studies on thiophene acetylide Ru(II) complexes for nonlinear optics: structure-function relationships and solvent effects - Mendes, Paulo J. (2012)
Density functional theory (DFT) calculations were employed to investigate the second-order nonlinear optical (SONLO) properties of η5-monocyclopentadienylruthenium(II) thiophene acetylide complexes. From molecular structure, electronic states, and optical absorption spectra, we have studied the effect of donor or acceptor substituents in thiophene ligands on their first hyperpolarizabilities in vacuum. Calculations in solvated media have also been performed for the complex with the highest first hyperpolarizability obtained in vacuum. The results reveal a significant influence of solvation on the first hyperpolarizability of this compound. The improvement of the second-order nonlinear optical properties in solvated media is due not only to the change of the excitation energies but also to the increase of ground-state molecular polarization and efficiency of metal-to-ligand charge transfer for electronic excitations.